2018
DOI: 10.1002/asjc.1823
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Control for Stochastic Multi‐Agent Systems Based on Hybrid Event‐Triggered Mechanism

Abstract: This paper deals with the leader‐following consensus for nonlinear stochastic multi‐agent systems. To save communication resources, a new centralized/distributed hybrid event‐triggered mechanism (HETM) is proposed for nonlinear multi‐agent systems. HETMs can be regarded as a synthesis of continuous event‐triggered mechanism and time‐driven mechanism, which can effectively avoid Zeno behavior. To model the multi‐agent systems under centralized HETM, the switched system method is applied. By utilizing the proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
(70 reference statements)
0
27
0
Order By: Relevance
“…Consider the Itô stochastic system (7) with assumption 1, and sliding surface described by (8) with G = B T where satisfies the LMI described in (15). Then, it can be shown that the mean-square reachability of the sliding surface (8) is assured by SMC law (20) and condition (21):…”
Section: Stochastic Sliding Mode Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the Itô stochastic system (7) with assumption 1, and sliding surface described by (8) with G = B T where satisfies the LMI described in (15). Then, it can be shown that the mean-square reachability of the sliding surface (8) is assured by SMC law (20) and condition (21):…”
Section: Stochastic Sliding Mode Controllermentioning
confidence: 99%
“…There are plenty of studies trying to tackle with stabilizing and control of Itô models through designing an idiosyncratic control strategy. See, for instance [16,17], for stability results, and [18][19][20] for some recent control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to avoid unexpected obstacles using a specific obstacle avoidance scheme, the robot may not consider the behavior of other robots while avoiding obstacles. In order to allow robots to consider the behavior of other robots instantly and continuously, it is desirable to allow robots to communicate, cooperate, and navigate in the environment for the multiple robot coordination [15‐19]. The coordinating framework of obstacle avoidance and navigation control demands urgent attention for multi‐robot applications.…”
Section: Introductionmentioning
confidence: 99%
“…Before the year 2000, H ∞ control for both linear and nonlinear deterministic systems has been extensively studied [3]. In recent years, due to a great many of system models being expressed by Itô-type stochastic differential equations [4][5][6][7][8], stochastic H ∞ control of Itô-type differential systems has become a popular research topic and attracted a great deal of attention; see the monographs [9][10][11][12] and the references [13][14][15][16][17][18]. It should be mentioned that, except for the study of standard stochastic Itô systems, singular stochastic Itô systems and switching stochastic systems have also been studied in the directions of stochastic stability, stabilization, H 2 optimal control and H ∞ control; see [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%